Comparative Analysis of Financial Performance of Sharia Banks and Conventional Banks - Anton Priyo Nugroho (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This research objective is to determine the comparison of the economic performance of Sharia Banks and Conventional Banks. This study was conducted at sharia banking and conventional banking institutions indexed on the Indonesia Stock Exchange in 2018-2022. This type of studies is quantitative, the type of information used is secondary data, the statistical collection method used is documentation strategies and the information analysis method is quantitative descriptive methods. The population used is all banks in Indonesia. Meanwhile, figuring out the sample used the purposive sampling method. The records evaluation method was done using the descriptive evaluation testing degree and unbiased pattern t-test evaluation. The research results show that there may be no big distinction between the financial performance of Sharia Banks and Conventional Banks within the 2018-2022 duration.